Solving Min-Max Capacitated Vehicle Routing Problem by Local Search - Nguyen, Son Van; Pham, Dung Quang; Bui, Trung Quoc; Nguyen, Hoang Thanh (Journal of Computer Science and Cybernetics, 2017)
Vehicle routing is a class of combinatorial optimization problems in transportation and logistics. Min-max capacitated vehicle routing is a problem of this class in which the length of the longest route must be minimized. This paper investigates local search approach for solving the min-max capacitated vehicle routing problem with different neighborhood structures. We also propose a combined function instead of the objective function itself for controlling the local search. Experimental results on different datasets show the efficiency of our proposed algorithms compared to previous techniques.